السلطة التنفيذية في التعديل الدستور 2016 - عرامي, فرحات; عمامرة, العطرة (University of Eloued جامعة الوادي, 2017)
السلطة التنفيذية هي سلطة من سلطات النظام السياسي، و هي الأقوى، تتكون من شقين، الشق الأول رئيس الجمهورية و الشق الثاني رئيس الحكومة الذي تغيرت تسميته إلى الوزير الأول ابتداء من التعديل الدستوري 2008 و عُزز في التعديل الأخير 2016. و يمتاز رئيس الجمهورية فيها بمركز قوي جدا إكتسبه من خلال آلية انتخابه السرية و المباشرة، وهو حجر الزاوية و ركيزة النظام السياسي، وهو رئيس الجهاز التنفيذي فيه، و أصبحت مؤسسة الرئاسة أقوى مؤسسة دستورية في البلاد، يتمتع رئيسها بصلاحيات واسعة جدا في الظروف العادية و غير العادية، و كل هذا النفوذ و الهيمنة نجد الدستور حصانه و أعفاه من المسؤولية السياسية، و أقر له المسؤولية الجنائية الموقوفة التنفيذ إلى أجل غير مسمى. أما الشق الثاني في السلطة التنفيذية فقد جرد من كل صلاحياته الدستورية، و أصبح أول وزير في حكومة الرئيس، و ما هو إلا منسق عمل الحكومة و منفذ مخطط العمل، وليس له حرية التصرف إلا بعد إذن رئيس الجمهورية، و برغم فقدانه للسلطة إلا أنه يتحمل المسؤولية السياسية أمام رئيس الجمهورية و البرلمان، و المسؤولية الجنائية عن الجنايات و الجنح التي يرتكبها أثناء أداء مهامه إلا أن هذه المسؤولية بقية موقوفة التنفيذThe executive branch is one of the authorities of the political system and it is the strongest. The executive branch consists of two parts: the first part is the president and the second part is thehead of government whose name has been changed to the prime minister from the constitutional amendment of 2008 and reinforced in the last amendment of 2016. The President of the Republic has a very strong position gained by the mechanism of his secret and direct election. The President of the Republic is the head of the executive branch and he is the cornerstone and pillar of the political system.The presidency became the most powerful constitutional institution in the country andits president has very wide powers under ordinary and extraordinary circumstances.The constitution immunes and exempts the President of the Republic from any political liability. However, the constitution granted the criminal liability but it suspended indefinitely. The second part of the executive branch is the prime minister. He isa minister in the government of the president. The prime minister is the coordinator of the government and the executor of the work plan. He is not allowed to produce any order without prior president's permission. The prime minister bears the political liability ahead the President of the Republic and the Parliament. As well as the criminal liability for the crimes and misdemeanors committed by him in the performance of his duties. However, this liability shall remain suspended. .
مدكرة ماستر